IMPLEMENTASI PERLINDUNGAN KORBAN KEKERASAN DALAM RUMAH TANGGA MELALUI KEADILAN RESTORATIF DI KEPOLISIAN DAERAH JAWA TIMUR - Daniel Mangara Tua Pandiangan; Maria Novita Apriyani (Universitas Labuhanbatu, 2026)
The increasing incidence of domestic violence (DV) in Indonesia indicates that legal protection for victims continues to face significant challenges, particularly in ensuring case resolution mechanisms that not only emphasize the punishment of offenders but also guarantee victims' recovery, safety, and access to justice. Within this context, restorative justice has emerged as an alternative approach implemented during the criminal investigation process to resolve certain domestic violence cases. This study aims to analyze the implementation of victim protection through restorative justice during the investigation stage at the East Java Regional Police (Polda Jawa Timur), evaluate the fulfillment of victims' rights throughout the case resolution process, and identify the obstacles affecting the effectiveness of victim protection. The research employed a normative-empirical (socio-legal) approach, using statutory, conceptual, and empirical approaches through document analysis and interviews with investigators and other relevant stakeholders. The findings indicate that victim protection has been implemented through compliance with formal and substantive requirements, the conduct of restorative mediation, and the termination of investigations when agreements adequately safeguarding victims' interests are reached. However, the effectiveness of victim protection remains constrained by unclear procedural time limits, varying interpretations among investigators regarding the application of restorative justice, the psychological vulnerability of victims, and technical challenges encountered during the mediation process. These obstacles have prevented the optimal implementation of victim protection, highlighting the need for clearer implementation guidelines, enhanced investigators' capacity, and stronger inter-agency coordination to ensure more effective protection for victims of domestic violence.Keywords: victim protection; domestic violence; restorative justice; criminal investigation; East Java Regional Police.